Adenoviral Respiratory Infection-Associated Mortality in Children: A Retrospective Case Series - Spaeder, Michael C.; Stewart, Claire; Sharron, Matthew P.; Noether, Julia R.; Martinez-Schlurman, Natalia; Kavanagh, Robert P.; Signoff, Jessica K.; McCrory, Michael C.; Eidman, Daniel B.; Subbaswamy, Anjali V.; Shea, Paul L.; Harwayne-Gidansky, Ilana; Ninmer, Emily K.; Sheram, Mary Lynn; Watson, Christopher M. (Journal of Pediatric Intensive Care, 2020)
Viral respiratory infections are a leading cause of illness and hospitalization in young children worldwide. Case fatality rates in pediatric patients with adenoviral lower respiratory tract infection requiring intensive care unit (ICU) admission have been reported between 7 and 22%. We investigated the demographics and clinical characteristics in pediatric mortalities associated with adenoviral respiratory infection at 12 academic children's hospitals in the United States. There were 107 mortality cases included in our study, 73% of which had a chronic medical condition. The most common chronic medical condition was immunocompromised state in 37 cases (35%). The incidences of pediatric acute respiratory distress syndrome (78%) and multiple organ dysfunction syndrome (94%) were profound. Immunocompetent cases were more likely to receive mechanical ventilation within the first hour of ICU admission (60 vs. 14%, p < 0.001) and extracorporeal membrane oxygenation (27 vs. 5%, p = 0.009), and less likely to receive continuous renal replacement therapy (20 vs. 49%, p = 0.002) or have renal dysfunction (54 vs. 78%, p = 0.014) as compared with immunocompromised cases. Immunocompromised cases were more likely to have bacteremia (57 vs. 16%, p < 0.001) and adenoviremia (51 vs. 17%, p < 0.001) and be treated with antiviral medications (81 vs. 26%, p < 0.001). We observed a high burden of nonrespiratory organ system dysfunction in a cohort of pediatric case fatalities with adenoviral respiratory infection. The majority of cases had a chronic medical condition associated with an increased risk of complications from viral respiratory illness, most notably immunocompromised state. Important treatment differences were noted between immunocompromised and immunocompetent cases.
Keywords: respiratory tract infections; adenovirus; intensive care; children; pediatric